2016
DOI: 10.3389/fpls.2016.01116
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal, Sex- and Plant Size-Related Effects on Photoinhibition and Photoprotection in the Dioecious Mediterranean Dwarf Palm, Chamaerops humilis

Abstract: In Mediterranean-type ecosystems plants are exposed to several adverse environmental conditions throughout the year, ranging from drought stress during the warm and dry summers to chilling stress due to the typical drop in temperatures during winters. Here we evaluated the ecophysiological response, in terms of photoinhibition and photoprotection, of the dioecious Mediterranean palm, Chamaerops humilis to seasonal variations in environmental conditions. Furthermore, we considered as well the influence of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…Contrary to our first hypothesis, higher F v /F m in needles of female individuals indicates that they had a potentially higher capacity of light absorption, but it also means that they had been adapted to the low light environment and were thus more threatened by photoinhibition when exposed to high light compared with males (Maxwell and Johnson, 2000 ; Wyka et al, 2007 ). Our results are in agreement with the earlier findings of Xu et al ( 2008 ) and Morales et al ( 2016 ) suggesting that females are generally more sensitive to photoinhibition than males.…”
Section: Discussionsupporting
confidence: 94%
“…Contrary to our first hypothesis, higher F v /F m in needles of female individuals indicates that they had a potentially higher capacity of light absorption, but it also means that they had been adapted to the low light environment and were thus more threatened by photoinhibition when exposed to high light compared with males (Maxwell and Johnson, 2000 ; Wyka et al, 2007 ). Our results are in agreement with the earlier findings of Xu et al ( 2008 ) and Morales et al ( 2016 ) suggesting that females are generally more sensitive to photoinhibition than males.…”
Section: Discussionsupporting
confidence: 94%
“…A decrease in the F v / F m values below 0.8 has been considered symptomatic of stress‐dependent photoinhibition (Björkman and Demmig, ; Kalaji et al., ). In this regard, winter photoinhibition is a recognized phenomenon in some Mediterranean species, as a consequence of the low temperatures, short photoperiods, and clear days with elevated irradiance (Oliveira and Peñuelas, ; Morales et al., ). Our findings suggest a negative effect of low temperature on the photochemical performance of both taxa, particularly on the efficiency of capture of the excitation energy by open PSII reaction centers (Krause and Weis, ; Mohammed et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we found no signs of gender dimorphism in the photosynthetic response. Other studies have found signs of higher photoinhibition in female plants of dioecious species, associated to the reproductive period and drought stress, as it has been reported in the dwarf palm Chamaerops humilis (Morales et al, 2016) and in the subdioecious species Honckenya peploides (Sánchez-Vilas and Retuerto, 2011). Or what is more, when comparing reproductive and non-reproductive shoots of female Pistacia lentiscus, higher photoinhibition was observed in reproductive shoots (Juvany et al, 2014).…”
Section: 2physiological Responsesmentioning
confidence: 58%
“…On the other hand, in order to produce pollen, male plants should need more nitrogen supply than females, which may lead to different resource demands (Barrett and Hough, 2013); these differences should be more important in wind-pollinated plants during the flowering period, generating a trade-off in the investment of growth and reproduction (Obeso, 2002;Zunzunegui et al, 2006). In relation to these ideas, in the literature there are many studies on gender distribution, morphology, growth and survival in dioecious plants (Allen and Antos, 1993;Álvarez-Cansino et al, 2010a;Diaz-Barradas and Correia, 1999;Herrera, 1988;Morales et al, 2016;Nicotra, 1999;Obeso, 1997;Zunzunegui et al, 2006). Yet, studies on genderspecific physiology in dioecious species are limited (Álvarez-Cansino et al, 2012;Álvarez-Cansino et al, 2010b;Correia and Díaz Barradas, 2000;Dawson et al, 2004;Dawson and Ehleringer, 1993;Juvany et al, 2014;Juvany and Munné-Bosch, 2015;Sánchez-Vilas and Retuerto, 2009).…”
Section: Introductionmentioning
confidence: 99%